Model Penentuan Nilai Mahasiswa Pada Aspek Partisipasi Belajar Dengan Pendekatan Fuzzy Tsukamoto - Kesuma, Novriyanti Kesuma; Armansyah, Armansyah; Suhardi, Suhardi (Jurnal Pseudocode, 2025)
This study aims to determine the model of student learning participation value and also to determine the criteria for student participation that triggers the value of student learning participation. This study has 5 variables, namely attendance participation, questioning participation, giving ideas participation, helping friends and group discussion activity, each of which has a certain weight. The application of fuzzy logic in this assessment uses fuzzy tsukamoto, the fuzzy rules obtained are 46 rules. The defuzzification results get 87.47 with a very good category, so out of 31 participants who get a fairly good category are 21 participants, participants who get a good category are 9 participants and those who get a very good category are 1 participant.